Are imports in Africa responsive to tariff reductions? - Chris Jones; Oliver Morrissey (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2008)
In the 1980's and 1990's many African countries liberalised their trade policy, although since the mid 1990s there are countries that did not alter tariffs. This allows us to analyse the effects of trade liberalisation on the change in imports using Difference-in-Differences techniques that allow us to evaluate the impact on imports of trade liberalisation at the general and sector-specific level. During the period of study (1996-2004), Algeria (in 1997), Ethiopia (2001), Egypt (1998), Tanzania (2000) and Uganda (2000) all liberalised their tariffs. These countries act as a 'treatment' group. In comparison, Cameroon, Gabon and Madagascar all left their tariffs unchanged. These countries act as our 'control' group or counterfactual. We compare the effects on imports for liberalising countries relative to non-liberalising countries, controlling for the timing of liberalisation, trends in import capacity (country effects) and in sector imports across countries (product market effects). Overall, using three methods of measuring imports, there is little evidence that suggests imports increased for the treatment group countries relative to the control group countries. This is true at the general and sector-specific levels.
Keywords: 330; Tariffs; Difference-in-Difference; Liberalisation; Africa; Außenhandelsliberalisierung; Zolltarif; Importnachfrage; Branche; Afrika